A lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film and its preparation method and application

By using lignin nanobottles and chitin nanocrystals as nanoreinforced fillers in seawater desalination film materials, combined with polyvinyl alcohol, nanocomposite films with excellent mechanical, antibacterial and photothermal conversion performance are prepared, which solves the problems of complex machinery, high energy consumption and insufficient membrane material performance in existing seawater desalination technologies, and achieves efficient and energy-saving seawater desalination effects.

CN117903473BActive Publication Date: 2025-04-08QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410082175.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-19
Publication Date
2025-04-08
Estimated Expiration
2044-01-19

AI Technical Summary

Technical Problem

The existing seawater desalination technology has problems such as complex mechanical equipment, high energy consumption, and insufficient antibacterial, mechanical and photothermal conversion performance of membrane materials.

Method used

The lignin nanoflask and chitin nanocrystals were used as nanoreinforced fillers and combined with polyvinyl alcohol to prepare a lignin nanoflask/chitin nanocrystals/polyvinyl alcohol nanocomposite film. The membrane material improves mechanical properties, antibacterial properties and photothermal conversion properties through specific preparation methods.

Benefits of technology

It improves the mechanical properties, antibacterial properties and photothermal conversion properties of the nanocomposite membrane, has high degradability, and is suitable for seawater desalination evaporation membrane, achieving efficient and energy-saving seawater desalination effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117903473B_ABST
    Figure CN117903473B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer materials, and in particular to a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film and a preparation method and application thereof. The present invention utilizes lignin nanobottles and chitin nanocrystals as binary nano-reinforced fillers, which not only improves the mechanical properties of the nanocomposite film, but also has excellent antibacterial and anti-ultraviolet properties, and has high photothermal conversion performance. Therefore, the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film provided by the present invention is expected to be used as a seawater desalination evaporation membrane in seawater desalination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film and a preparation method and application thereof. Background Art

[0002] Nearly 70% of the Earth's surface is covered by oceans, which contain more than 1.36×10 18 Cubic meters. However, the freshwater resources available for direct human use only account for 0.04% of the world's total water. Freshwater ecosystems are the basis for the survival of animals and plants. With the deterioration of the climate and the rapid economic growth, many rivers, lakes and groundwater resources have been severely damaged by modern industrial activities, and the problem of global water shortage has become increasingly prominent.

[0003] Seawater desalination is an effective way to solve the global water shortage. Traditional seawater desalination technologies are mainly thermal distillation and reverse osmosis. However, both thermal distillation and reverse osmosis methods require the use of various complex mechanical equipment and consume a large amount of fossil energy. Therefore, exploring efficient, energy-saving and economical seawater desalination processes to meet the needs of daily production is still a technical problem that urgently needs to be solved.

[0004] Solar energy is an inexhaustible, renewable, clean energy source. The solar radiation power of the sun shining on the earth's surface is as high as 1.73×10 17 W, far exceeding the annual power generation of humans, and theoretically can provide sufficient energy consumption. It is worth noting that photothermal conversion is the most reliable way to utilize solar energy, because photothermal materials can convert the energy of absorbed photons into thermal energy, which can effectively increase the temperature of the surrounding environment and realize the utilization of solar energy. In recent years, the use of solar photothermal conversion principles to evaporate seawater can efficiently obtain a large amount of clean drinking water at lower temperatures and pressures, which is impossible with traditional thermal evaporation and reverse osmosis technologies. Therefore, it has become a promising development trend in clean fresh water production. This new green technology also provides a low-cost and effective way to solve the problem of water scarcity.

[0005] Although some membrane materials for seawater desalination are disclosed in the prior art, they have poor antibacterial properties, poor mechanical properties, poor photothermal conversion properties and cannot be degraded. Summary of the invention

[0006] In order to overcome the above problems, the present invention provides a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film and a preparation method and application thereof. The present invention uses lignin nanobottles and chitin nanocrystals as binary nano-reinforced fillers, which not only improves the mechanical properties of the nanocomposite film, but also has excellent antibacterial and anti-ultraviolet properties, and has high photothermal conversion performance. Therefore, the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film provided by the present invention is expected to be used as a seawater desalination evaporation membrane in seawater desalination.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a method for preparing a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film, comprising:

[0009] (1) adding purified lignin to an aqueous solution of γ-butyrolactone, mixing well, dropping the mixed solution into deionized water to obtain a lignin nanobottle suspension, dialyzing to remove γ-butyrolactone, and freeze-drying to obtain a lignin nanobottle;

[0010] (2) adding chitosan to a low eutectic solvent, stirring the reaction, washing the solid precipitate by centrifugation for multiple times, dispersing the precipitate again in deionized water, and then ultrasonically treating the precipitate with an ultrasonic cell disruptor to obtain a chitosan nanocrystal suspension;

[0011] (3) dispersing polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol solution, adding the lignin nanobottle obtained in step (1) and the chitin nanocrystal suspension obtained in step (2) to the polyvinyl alcohol solution, mixing them evenly, and air-drying the mixed solution to form a film to obtain a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film.

[0012] The second aspect of the present invention provides a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film prepared by the above preparation method.

[0013] The third aspect of the present invention provides the use of the above-mentioned lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film in solar-driven seawater desalination.

[0014] The beneficial effects of the present invention are:

[0015] (1) The raw materials of the nanocomposite film in the present invention, lignin, chitin and polyvinyl alcohol are all degradable. At the same time, the interaction between lignin nanobottles and chitin nanocrystals as nano-reinforced fillers greatly improves the mechanical properties of the nanocomposite film. Lignin nanobottles can not only expose more antibacterial active sites, but also increase the contact area with bacteria. Chitin nanocrystals themselves also have a certain antibacterial effect. The synergistic effect of the two gives the composite film excellent antibacterial properties. Due to the unique nanobottle structure of the lignin nanobottle, the lignin nanobottle has a large light absorption cross-section, so the composite film has excellent photothermal conversion performance and UV resistance.

[0016] (2) The nanocomposite film prepared by the present invention has a tensile stress of 65 MPa and an ultra-high elongation at break of up to 611.5%, which effectively solves the current problem of poor mechanical properties of polyvinyl alcohol and greatly expands the application scope of the film.

[0017] (3) The temperature of the nanocomposite membrane prepared by the present invention is measured by an infrared camera, which can reach 62.1°C under the optimal conditions. It has excellent light conversion efficiency and is therefore expected to be used as a desalination evaporation membrane in seawater desalination. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0019] Figure 1 This is a scanning electron microscope image of the lignin nanobottle prepared in Example 1;

[0020] Figure 2 This is an AFM image of chitin nanocrystals prepared in Example 1;

[0021] Figure 3 These are the light-to-heat conversion performance test results of the comparative example 1 in experimental example 1 and the nanocomposite film prepared in embodiment 4. DETAILED DESCRIPTION

[0022] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0023] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0024] The first typical embodiment of the present invention provides a method for preparing a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film, comprising:

[0025] (1) adding purified lignin to an aqueous solution of γ-butyrolactone, mixing well, dropping the mixed solution into deionized water to obtain a lignin nanobottle suspension, dialyzing to remove γ-butyrolactone, and freeze-drying to obtain a lignin nanobottle;

[0026] (2) adding chitosan to a low eutectic solvent, stirring the reaction, washing the solid precipitate by centrifugation for multiple times, dispersing the precipitate again in deionized water, and then ultrasonically treating the precipitate with an ultrasonic cell disruptor to obtain a chitosan nanocrystal suspension;

[0027] (3) dispersing polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol solution, adding the lignin nanobottle obtained in step (1) and the chitin nanocrystal suspension obtained in step (2) to the polyvinyl alcohol solution, mixing them evenly, and air-drying the mixed solution to form a film to obtain a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film.

[0028] In one or more embodiments, in step (1), the volume ratio of γ-butyrolactone to deionized water in the aqueous solution of γ-butyrolactone is 8 to 10:1, preferably 9:1.

[0029] In one or more embodiments, in step (1), based on 50 mg of purified lignin, the amount of the aqueous solution of γ-butyrolactone is 4 to 6 mL, and the amount of deionized water is 16 to 24 mL.

[0030] In one or more embodiments, in step (1), the molecular weight cutoff of the dialysis bag is 1000 Mw, and the dialysis time is 48 to 96 h.

[0031] In one or more embodiments, in step (2), the low eutectic solvent is choline chloride-lactic acid, and the molar ratio of choline chloride to lactic acid is 1.5 to 2.5:1, preferably 2:1.

[0032] In one or more embodiments, in step (2), the mass ratio of chitosan to the deep eutectic solvent is 1:20 to 30, preferably 1:25.

[0033] In one or more embodiments, in step (2), the stirring reaction temperature is 90 to 110° C., preferably 100° C., and the stirring reaction time is 0.5 to 3 h, preferably 1 h.

[0034] In one or more embodiments, in step (2), the solid precipitate is washed with water by centrifugation multiple times until the pH value of the dispersion is 6-7.

[0035] In one or more embodiments, in step (2), after the precipitate is dispersed again in deionized water, the concentration is 0.3-0.8 wt %, preferably 0.5 wt %.

[0036] In one or more embodiments, in step (2), the power of the ultrasonic cell disruptor for ultrasonic treatment is 700-900 W, preferably 800 W, and the time of ultrasonic treatment is 25-40 min, preferably 30 min.

[0037] In one or more embodiments, in step (3), the temperature of the polyvinyl alcohol solution in which polyvinyl alcohol is dispersed in deionized water and stirred is 80-100° C., preferably 90° C., and the stirring time is 2.5-4 h, preferably 3 h.

[0038] In one or more embodiments, in step (3), based on 1.5 g of polyvinyl alcohol, the amount of the lignin nanobottle is 1.5 to 75 mg, and the amount of the chitosan nanocrystal suspension is 2 to 3 mL.

[0039] In one or more embodiments, in step (3), the mass ratio of polyvinyl alcohol to deionized water is 1.5:28-30.

[0040] A second typical embodiment of the present invention provides a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film prepared by the above preparation method.

[0041] A third typical embodiment of the present invention provides the use of the above-mentioned lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film in solar-driven seawater desalination.

[0042] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0043] Example 1

[0044] (1) γ-butyrolactone and deionized water were mixed at a volume ratio of 9:1. After the mixture was uniformly mixed, 50 mg of purified lignin was added to 5 mL of the γ-butyrolactone aqueous solution. The lignin was completely dissolved by ultrasonication at room temperature for 5 min. 2 mL of the lignin solution was added dropwise to 8 mL of deionized water at room temperature to obtain a lignin nanobottle suspension. The lignin nanobottle suspension was transferred to a dialysis bag (with a molecular weight cutoff of 1000 Mw), and soaked in deionized water for 96 h to remove residual γ-butyrolactone. The lignin nanobottle was freeze-dried for use. The scanning electron microscope image of the lignin nanobottle is shown in FIG. Figure 1 As shown, the particle size of the lignin nanobottle is 108 nm and the bottle diameter is 38 nm.

[0045] (2) Add 2 g of chitosan powder to 50 g of a low eutectic solvent, choline chloride-lactic acid (molar ratio of 2:1), and mix under magnetic stirring at 100°C for 1 h. After the reaction is completed, quench the reaction by adding deionized water, centrifuge at 8000 rpm for 5 min, wash the solid precipitate with deionized water, and repeat the centrifugation and washing until the suspension becomes neutral. Collect the precipitate, disperse the undried chitosan sample after pretreatment in deionized water, dilute to a concentration of 0.5 wt%, and then use an ultrasonic cell disruptor (800 W) to ultrasonically treat the obtained chitosan nanocrystal suspension for use. The morphology of the prepared chitosan nanocrystals is as follows: Figure 2 shown.

[0046] (3) Disperse 1.5 g of polyvinyl alcohol powder into 28.5 mL of deionized water and stir at 90 °C for 3 h to obtain a polyvinyl alcohol solution. Add 1.5 mg of the lignin nanobottle obtained in step (1) and 2.5 mL of the chitin nanocrystal solution obtained in step (2) to the polyvinyl alcohol solution, stir for 30 min, then slowly pour 15 mL of the mixed solution into a plastic culture dish, air-dry at room temperature to form a film to obtain a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film.

[0047] Example 2

[0048] The preparation method of the lignin nanobottle and chitin nanocrystal suspension is the same as that in Example 1.

[0049] 1.5 g of polyvinyl alcohol powder was dispersed in 28.5 mL of deionized water and stirred at 90 ° C for 3 h to obtain a polyvinyl alcohol solution. 15 mg of the lignin nanobottle obtained in step (1) and 2.5 mL of the chitin nanocrystal solution obtained in step (2) were added to the polyvinyl alcohol solution, stirred for 30 min, and 15 mL of the mixed solution was slowly poured into a plastic culture dish, and air-dried at room temperature to form a film to obtain a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film.

[0050] Example 3

[0051] The preparation method of the lignin nanobottle and chitin nanocrystal suspension is the same as that in Example 1.

[0052] 1.5 g of polyvinyl alcohol powder was dispersed in 28.5 mL of deionized water and stirred at 90 ° C for 3 h to obtain a polyvinyl alcohol solution. 30 mg of the lignin nanobottle obtained in step (1) and 2.5 mL of the chitin nanocrystal solution obtained in step (2) were added to the polyvinyl alcohol solution, stirred for 30 min, and 15 mL of the mixed solution was slowly poured into a plastic culture dish, and air-dried at room temperature to form a film to obtain a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film.

[0053] Example 4

[0054] The preparation method of the lignin nanobottle and chitin nanocrystal suspension is the same as that in Example 1.

[0055] 1.5 g of polyvinyl alcohol powder was dispersed in 28.5 mL of deionized water and stirred at 90 ° C for 3 h to obtain a polyvinyl alcohol solution. 75 mg of the lignin nanobottle obtained in step (1) and 2.5 mL of the chitin nanocrystal solution obtained in step (2) were added to the polyvinyl alcohol solution, stirred for 30 min, and 15 mL of the mixed solution was slowly poured into a plastic culture dish, and air-dried at room temperature to obtain a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film.

[0056] Comparative Example 1

[0057] 1.5 g of polyvinyl alcohol powder was dispersed in 28.5 mL of deionized water and stirred at 90° C. for 3 h to obtain a polyvinyl alcohol solution. 15 mL of the polyvinyl alcohol solution was slowly poured into a plastic petri dish and air-dried at room temperature to form a film to obtain a pure polyvinyl alcohol film.

[0058] Comparative Example 2

[0059] (1) The preparation method of chitosan nanocrystal suspension is the same as that in Example 1.

[0060] (2) 1.5 g of polyvinyl alcohol powder was dispersed in 28.5 mL of deionized water and stirred at 90 °C for 3 h to obtain a polyvinyl alcohol solution. 2.5 mL of chitosan nanocrystal solution was added to the polyvinyl alcohol solution and stirred for 30 min. 15 mL of the mixed solution was slowly poured into a plastic petri dish and air-dried at room temperature to obtain a chitosan nanocrystal / polyvinyl alcohol nanocomposite film.

[0061] Experimental Example 1

[0062] The nanocomposite films prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were characterized.

[0063] (1) Mechanical properties test: The tensile test of the nanocomposite film was carried out at ambient temperature using a mass spectrometer (Stable Micro Systems, TA-XTplusC, Germany). The composite film was made into a rectangular sample (length = 30 mm, width = 10 mm) and the tensile strength was 20 mm / min. -1 The speed used for tensile tests

[0064] The mechanical properties test results are shown in Table 1.

[0065] Table 1 Mechanical properties test results of the nanocomposite films prepared in Examples 1 to 3 and Comparative Examples 1 and 2

[0066]

[0067] (2) Antibacterial performance test: The nanocomposite membrane was first wiped with anhydrous ethanol solution and placed on a sterilized clean workbench. Then 100 μL of bacterial suspension was evenly spread on the nanocomposite membrane sample and placed in a 37°C incubator for 24 hours. After that, the nanocomposite membrane sample was washed with 0.8 wt% sodium chloride solution, shaken, and 100 μL was inoculated on agar medium. Then the culture medium was cultured in a 37°C incubator for 24 hours. Finally, the bacterial growth on the culture medium was observed and compared with the control.

[0068] The antibacterial performance test results are shown in Table 2.

[0069] Table 2 Antibacterial performance test results of the nanocomposite films prepared in Example 1 and Comparative Examples 1 and 2

[0070]

[0071] It can be seen from Table 2 that the nanocomposite film provided by the present invention has good antibacterial properties.

[0072] (3) UV shielding rate test: The UV shielding performance of the film was determined by measuring the emission spectrum within the wavelength range of 200 nm to 800 nm using a UV-visible spectrophotometer (UV-2600, Shimadzu, Japan).

[0073] The results are shown in Table 3.

[0074] Table 3 Ultraviolet shielding rate of the nanocomposite films prepared in Examples 1 to 4 and Comparative Examples 1 and 2

[0075]

[0076] (4) Photothermal conversion performance test: 1 sun intensity (100mW / cm 2) light source equipment to illuminate the sample for 10 minutes and use an infrared thermal imager (Fotric 615c) to measure the light-to-heat conversion performance of the film, and record the infrared image of the temperature change of the film.

[0077] The results are shown in Table 4 and Figure 3 shown.

[0078] Table 4 Test results of the photothermal conversion performance of the nanocomposite films prepared in Examples 1 to 4 and Comparative Examples 1 and 2

[0079]

[0080]

[0081] As shown in Table 1, the synergistic effect of the hydrogen bonding force, π-π force, charge force and other interaction forces between chitin nanocrystals and lignin nanobottles greatly improves the mechanical properties of the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film compared with the control. With the increase of the content of lignin nanobottles, the interaction force is further enhanced, which further improves the tensile stress and elongation at break.

[0082] As shown in Table 2, chitosan nanocrystals as cationic substances have certain antibacterial properties against anionic bacteria. The polyphenol side chains of lignin have an inhibitory effect on bacterial growth. At the same time, the unique nanobottle structure of lignin nanobottles not only exposes more active sites, but also increases the contact area with bacteria, significantly improving the antibacterial properties of the composite film.

[0083] As shown in Tables 3 and 4, the large amount of void space in the lignin nanobottle structure improves the radiation absorption efficiency through the "light capture" effect, which ultimately makes the composite film material have excellent ultraviolet shielding properties and light-to-heat conversion properties.

[0084] By comparing the performance of the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite films obtained in the above examples and comparative examples, it can be clearly seen that the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film prepared by the technical solution provided by the present invention has excellent mechanical properties, antibacterial properties, UV shielding properties and photothermal conversion properties.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film, characterized in that: include: (1) adding purified lignin to an aqueous solution of γ-butyrolactone, mixing well, dropping the mixed solution into deionized water to obtain a lignin nanobottle suspension, dialyzing to remove γ-butyrolactone, and freeze-drying to obtain a lignin nanobottle; (2) adding chitosan to a low eutectic solvent, stirring the reaction, washing the solid precipitate by centrifugation for multiple times, dispersing the precipitate again in deionized water, and then ultrasonically treating the precipitate with an ultrasonic cell disruptor to obtain a chitosan nanocrystal suspension; (3) dispersing polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol solution, adding the lignin nanobottle obtained in step (1) and the chitin nanocrystal suspension obtained in step (2) to the polyvinyl alcohol solution, mixing them evenly, and air-drying the mixed solution to form a film to obtain a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film; In step (1), the volume ratio of γ-butyrolactone to deionized water in the aqueous solution of γ-butyrolactone is 8 to 10:1; Or, in step (1), based on 50 mg of purified lignin, the amount of γ-butyrolactone aqueous solution is 4 to 6 mL, and the amount of deionized water is 16 to 24 mL; The deep eutectic solvent is choline chloride-lactic acid, and the molar ratio of choline chloride to lactic acid is 1.5-2.5:1; Or, the mass ratio of chitosan to the deep eutectic solvent is 1:20-30; Or, in step (2), the stirring reaction temperature is 90 to 110° C., and the stirring reaction time is 0.5 to 3 h; In step (2), the precipitate is dispersed again in deionized water to a concentration of 0.3 to 0.8 wt %; In step (3), based on 1.5 g of polyvinyl alcohol, the amount of the lignin nanobottle is 1.5 to 75 mg, and the amount of the chitin nanocrystal suspension is 2 to 3 mL.

2. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: In step (1), the volume ratio of γ-butyrolactone to deionized water in the aqueous solution of γ-butyrolactone is 9:

1.

3. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: In step (1), the molecular weight cutoff of the dialysis bag is 1000Mw, and the dialysis time is 48 to 96 hours.

4. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: The molar ratio of the choline chloride to the lactic acid is 2:

1.

5. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: The mass ratio of chitosan to the deep eutectic solvent is 1:

25.

6. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: In step (2), the stirring reaction temperature is 100°C.

7. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: In step (2), the stirring reaction time is 1 h.

8. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: In step (2), the solid precipitate is washed by centrifugation several times until the pH value of the dispersion is 6 to 7; Or, in step (2), the precipitate is dispersed again in deionized water to a concentration of 0.5 wt %.

9. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: In step (3), the temperature of the polyvinyl alcohol solution in which polyvinyl alcohol is dispersed in deionized water and stirred is 80 to 100° C., and the stirring time is 2.5 to 4 hours.

10. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: In step (3), the temperature of the polyvinyl alcohol solution in which polyvinyl alcohol is dispersed in deionized water and stirred is 90°C.

11. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: In step (3), the stirring time is 3 h.

12. The method for preparing the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 1, characterized in that: In step (3), the mass ratio of polyvinyl alcohol to deionized water is 1.5:28-30.

13. A lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film prepared by the method for preparing a lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to any one of claims 1 to 12.

14. Use of the lignin nanobottle / chitin nanocrystal / polyvinyl alcohol nanocomposite film according to claim 13 in solar-driven seawater desalination.

Citation Information

Patent Citations

  • Xanthoceras sorbifolia bunge nano lignin-based composite film and preparation method thereof

    CN115093587A